Utilization and Efficiency of eLearn Functionalities in a University (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study determined the utilization, satisfaction and perceived efficiency of the eLearning portal in a university known as eLearn. It is a web-based learning management system to aid classroom instruction that fosters self-directed learning. The mixed method of research was used in this study and utilized the researcher-made questionnaire as the main instrument. This employed the quota sampling procedure.  A total of 376 out of 9,130 college students were the participants of this study. The statistical tools utilized in the study consisted of Descriptive Statistics such as mean, standard deviations, frequency and percentages to describe the variables. Spearman’s rho ( ) was also utilized to determine the relationship of the variables under study. The findings revealed that the majority of the participants used eLearn, found it beneficial to their studies, were satisfied with the eLearn functionalities and perceived the functionalities as highly efficient.  The students' utilization of eLearn and satisfaction with the system's functionalities were not significantly associated with their perceived efficiency of the system. This implies that mere utilization of the eLearn does not predict their perception of efficiency.  The study concludes that eLearn in the university can be an effective tool in the teaching and learning processes and in the delivery of information resources. However, there is a need to encourage more teachers to maximize the utilization of this E-Learning portal. Furthermore, the study recommends that the findings be revealed to the administrators, Computing and Information Services Office, faculty and librarians so that through their combined efforts there would be more use of the eLearn.